Comparative Analysis of Sharia Stock Performance Before and During Covid-19 Pandemic in Indonesia - Ahmad Rasyid Al Faruk (Perbanas Institute, 2022)
The study analyzes the performance of sharia stocks before the Covid-19 pandemic and during the Covid-19 pandemic in Indonesia. The performance is measured using stock return and financial ratios. The financial ratios using in this study are return on equity (ROE), earnings per share (EPS), price to earnings ratio (PER), and price to book value (PBV). The data used in this study are collecting from the yahoo finance website and financial reports during the third quarter of 2019 and the third quarter of 2020. The type of research uses quantitative research. The sample uses 30 sharia stocks indexed in the Jakarta Islamic Index (JII) as of September 2020. The Wilcoxon signed-rank test use to testing the hypothesizes. The results show significant differences in stock return, ROE, EPS, and PBV between before the pandemic and during the Covid-19 pandemic in Indonesia. Meanwhile, in PER, there is no significant difference between the two comparison periods.